Kesalahan Bahasa dalam Naskah Dinas Satuan kerja Perangkat Daerah (SKPD) Kota Ternate - Noormala Noormala (Kantor Bahasa Provinsi Maluku Utara, 2015)
The study aims at to know the language error in SKPD official letter of Ternate City. Language error is focused at errors happend on parts of official letter. The method is qualitative method. It is a description of Indonesia language implementation. The collective data is done by using data card. The technique of collective data uses reading and writing technique. Then, it is analyzed and described. The result shows that language error found in them, namely heading, date, number, enclosure, concerning, address, the body of letter, writer’s identification, and copy.